Risk Management Implementation for Skincare Business Startup at PT Indo Bright Skincare - Mashudi, Daniel; Syah, Tantri Yanuar Rahmat; Pusaka, Semerdanta; Ramdhani, Dadan (International Journal of Social and Management Studies, 2021)
Skincare businesses in Indonesia continue to emerge, both large and small companies. Skincare products and local brand cosmetics still dominate Indonesian market. Local products have the opportunity to become the masters of the domestic market. People today are starting to be interested in skincare products made from natural ingredients such as tea extract, spices, or black garlic. Skincare products with black garlic ingredients have promising and potential business. PT Indo Bright Skincare offers skincare products made from black garlic extract. The company not only offers uniqueness by using black garlic extract, but the efficacy of this black garlic is also the selling point of the product. The establishment of a business has various risks. That’s why risk management is important for the company. By understanding risks, management can anticipate and manage risks properly.